Analysis of models for the Stochastic Outpatient Procedure Scheduling Problem - Shehadeh, Karmel S.; Cohn, Amy E.M.; Epelman, Marina A. (European journal of operational research, 2019)
•We propose a new model for the Stochastic Outpatient Procedure Scheduling Problem.•We compare our model to existing models both theoretically and empirically.•We show that significant improvements in performance can be gained with our model.•We show the importance of good models in solving mixed-integer programming problems. In this paper, we present a new stochastic mixed-integer linear programming model for the Stochastic Outpatient Procedure Scheduling Problem (SOPSP). In this problem, we schedule a day’s worth of procedures for a single provider, where each procedure has a known type and associated probability distribution of random duration. Our objective is to minimize the expectation of a weighted sum of patient waiting time, provider idling, and clinic overtime. We present computational results to show the size and characteristics of problem instances that can be solved with our model. We also compare this model to other formulations in the literature and analyze them both empirically and theoretically, demonstrating where significant improvements in performance can be gained with our proposed model. This work is motivated by our research on developing scheduling templates for endoscopic procedures at a major medical center. More broadly, however, the SOPSP is a stochastic single-resource sequencing and scheduling problem and therefore has applications both within and outside of healthcare operations.